Effects of process variables for biodiesel production by transesterification - Akgun, Nalan; Iscan, Emine (WILEY, 2007)
In this study, biodiesel production from various vegetable oils by transesterification was studied, to determine the optimum conditions. Experiments were carried out by using different kinds of catalysts (sodium hydroxide, potassium hydroxide, barium hydroxide, pyrolitic coke and wood ash) and feedstocks (corn oil, sunflower oil, soybean oil, olive pomace oil and cottonseed oil) at 65 degrees C and an agitation speed of 1000 rpm. The neutralization step with controlled pH was performed by treatment with phosphoric acid. An experimental design was used to evaluate the effects of the parameters such as types of vegetable oils, kinds of catalysts, reaction time, alcohol/oil volumetric ratio and amount of catalyst, on the methyl ester conversion. Using response surface methodology, a quadratic polynomial equation was obtained by multiple regression analysis. It was found that catalyst concentration was the most effective parameter. Sodium hydroxide and potassium hydroxide exhibited a superior catalytic behavior, whereas pyrolitic coke and wood ash had to be used in excess amount or for prolonged reaction times. Moreover, the properties such as viscosity, density, calorific value, acid value, and refractive index of the biodiesel were measured. The tri-, di-, monoacylglycerols and glycerol residuals in the methyl esters produced were also quantified by GC analysis.
Keywords: biodiesel; experimental design; glycerol; response surface methodology; vegetable oil; VEGETABLE-OIL; FUEL; Food Science & Technology; Nutrition & Dietetics